Matter of Time: Early Versus Late Percutaneous Coronary Intervention in Acute Coronary SyndromeObjective: To find the outcomes of patients undergoing early versus late percutaneous coronary intervention after Acute Myocardial Infarction. Study Design: Cro (Medical Forum Monthly, 2022)
Objective: To find the outcomes of patients undergoing early versus late percutaneous coronary intervention after Acute Myocardial Infarction.Study Design: Cross sectional StudyPlace and Duration of Study: This study was conducted at Cardiology Unit of Qazi Hussain Ahmed Medical Institute, Nowshera from January 2021 to June 2021 for a period of six months.Materials and Methods: Study included 200 patients including 120 males. Mean age was 55±5.60 years. Patients presented with acute myocardial infarction, undergoing percutaneous coronary intervention were included. Patients were divided into two groups on the basis of time to intervention. Group 1 comprised of patients in which intervention was done in 24hr to 72 hrs, while Group 2 consisted of patients with intervention done after 7 days of presentation. Patients were then followed to look for primary outcomes like Myocardial infarction (STEMI, NSTEMI), cardiac death and angina in 6 months. Student t test and Chi Square used for analysis.Results: About 58.60% patients presented with STEMI while 41.40 % with NSTEMI. Group 1 consisted of 90 patients and Group 2 consisted of 110 patients. Mean EF of patients was 43.8±9%. Mean stent diameter was significantly smaller in group 1 (2.7±0.31 vs. 3.2±0.41 mm, p=0.04) while stent length was more in Group 2 (p=0.05). In total 12.5% patients had primary adverse events with cardiac mortality of 2.5%. On compilation, 13.33% of patients in the Group 1 and 15.45 % of patients in Group 2 suffered from primary adverse outcomes (p=0.11). Mortality rate was found not much different between the 2 groups (p=0.14).Conclusion: Percutaneous coronary intervention has no doubt greater benefit in patients with acute myocardial infarction but timings of intervention after 24hr of presentation especially in stable patients does not differ much.